2022
DOI: 10.3390/ijerph192215201
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation and Its Driving Forces of Soil Organic Carbon along an Urban–Rural Gradient: A Case Study of Beijing

Abstract: Rapid urbanization has reshaped land cover and the ecological environment, potentially improving or deteriorating soil organic carbon (SOC). However, the response of SOC to urbanization has not yet been fully exploited. Herein, by using the land-use transfer matrix, the Sen & Mann–Kendall tests, the Hurst index, and a geographical and temporal weighted regression (GTWR) model, as well as an urban–rural gradient perspective, we assessed the dynamic response of SOC to Beijing’s urbanization from 2001 to2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
0
0
Order By: Relevance
“…In addition, the closer the dry land is to the irrigation canal, the better the soil water and heat conditions are, which is conducive to the accumulation of SOC. Thus, the negative relation of Dis_RS and Dis_IC to SOC is proven [59][60][61], which is consistent with the results of this article.…”
Section: Impact Of Environmental Variables On Soc Variationsupporting
confidence: 92%
“…In addition, the closer the dry land is to the irrigation canal, the better the soil water and heat conditions are, which is conducive to the accumulation of SOC. Thus, the negative relation of Dis_RS and Dis_IC to SOC is proven [59][60][61], which is consistent with the results of this article.…”
Section: Impact Of Environmental Variables On Soc Variationsupporting
confidence: 92%
“…The encroachment of new buildings on a large area of cropland was the main feature of land use change in Beijing, and it mainly occurred in the plains. This feature was also confirmed by Liu et al [57] and Wang et al [55] in their studies on land use change in Beijing. As early as 2014, Zhao et al [58], by studying the spatial and temporal characteristics of cropland change in China over the past 30 years, found that the resultant decrease in cropland in China's peri-urban areas was mainly associated with an increase in building.…”
Section: Implications Of Spatiotemporal Variation Characteristics Of ...supporting
confidence: 76%
“…Regarding the assessment scale, the study of carbon storage has been expanded from single ecosystem types such as forest, grassland, and farmland to river basins, provinces, typical ecological areas, and urban agglomerations [16,[20][21][22]. Many studies have investigated the carbon emissions related to land use in large developed cities in East China, such as Beijing and Guangdong, and economically developed regions such as the Beijing-Tianjin-Hebei urban agglomeration, the Pearl River Delta urban agglomeration, and the Yangtze River Delta urban agglomeration [13,[23][24][25][26][27]. The results show that the optimization of the land use structure is an effective means of reducing carbon emissions [28,29].…”
Section: Introductionmentioning
confidence: 99%